The tumour suppressor OPCML promotes AXL inactivation by the phosphatase PTPRG in ovarian cancer - Antony, Jane; Zanini, Elisa; Kelly, Zoe; Tan, Tuan Zea; Karali, Evdoxia; Alomary, Mohammad; Jung, Youngrock; Nixon, Katherine; Cunnea, Paula; Fotopoulou, Christina; Paterson, Andrew; Roy‐Nawathe, Sushmita; et al. (EMBO reports, 2018)
In ovarian cancer, the prometastatic RTK AXL promotes motility, invasion and poor prognosis. Here, we show that reduced survival caused by AXL overexpression can be mitigated by the expression of the GPI‐anchored tumour suppressor OPCML. Further, we demonstrate that AXL directly interacts with OPCML, preferentially so when AXL is activated by its ligand Gas6. As a consequence, AXL accumulates in cholesterol‐rich lipid domains, where OPCML resides. Here, phospho‐AXL is brought in proximity to the lipid domain‐restricted phosphatase PTPRG, which de‐phosphorylates the RTK/ligand complex. This prevents AXL‐mediated transactivation of other RTKs (cMET and EGFR), thereby inhibiting sustained phospho‐ERK signalling, induction of the EMT transcription factor Slug, cell migration and invasion. From a translational perspective, we show that OPCML enhances the effect of the phase II AXL inhibitor R428 in vitro and in vivo . We therefore identify a novel mechanism by which two spatially restricted tumour suppressors, OPCML and PTPRG, coordinate to repress AXL‐dependent oncogenic signalling. Synopsis The GPI‐anchored tumour suppressor OPCML interacts with the oncogenic RTK AXL inducing its redistribution into cholesterol‐rich membrane domains. There, AXL is de‐phosphorylated by the resident phosphatase PTPRG, inhibiting AXL‐dependent signalling, motility and invasion. Binding of Gas6 to the oncogenic RTK AXL promotes its interaction with the tumour suppressor OPCML. The Gas6/AXL/OPCML complex accumulates in cholesterol‐rich lipid domains, where the phosphatase PTPRG de‐phosphorylates AXL. The coordinated action of OPCML and PTPRG blocks AXL signalling and inhibits Gas6‐stimulated motility and invasion in ovarian cancer cells. Graphical Abstract The GPI‐anchored tumour suppressor OPCML interacts with the oncogenic RTK AXL inducing its redistribution into cholesterol‐rich membrane domains. There, AXL is de‐phosphorylated by the resident phosphatase PTPRG, inhibiting AXL‐dependent signalling, motility and invasion.